SUSTAINABLE TOURISM MANAGEMENT AT POTENTIAL WORLD HERITAGE SITES: LAND USE ANALYSIS BY USING GIS: CASE STUDY: JERASH ARCHAEOLOGICAL SITE, JORDAN - Al-Saad, Saad (PEOPLE: International Journal of Social Sciences, 2017)
The current study aims to analyse the land use changes in the cultural landscape of Jerash Archaeological Site and identify the impacts of modern urbanization which influenced it, as a potential World Heritage Site, during the period between 1953 and 2016. This study employed Geographic Information System (GIS) as a main tool of the analysis. The results show that significant changes in land use have occurred. For instance, in 1953, the unused spaces have estimated at about 65.8%, whereas the modern urbanization areas covered 3.1%. In 2016, the unused spaces decreased to about 1.8%, while the modern urbanization areas increased significantly to 57.6%. These land use changes caused urban development encroachments which damaged and caused visual pollution to the archaeological and traditional remains. GIS mapping was used to produce archaeological zoning maps through delineating buffer zones around the City Wall area and the antiquities areas. Buffer zoning could be a rational guidance to policy makers and tourism planners to limit the urban encroachments onto the cultural landscape of Jerash archaeological site.